Proceedings of the 28th ACM International Conference on Information and Knowledge Management 2019
DOI: 10.1145/3357384.3357955
|View full text |Cite
|
Sign up to set email alerts
|

Commonsense Properties from Query Logs and Question Answering Forums

Abstract: Commonsense knowledge about object properties, human behavior and general concepts is crucial for robust AI applications. However, automatic acquisition of this knowledge is challenging because of sparseness and bias in online sources. This paper presents Quasimodo, a methodology and tool suite for distilling commonsense properties from non-standard web sources. We devise novel ways of tapping into search-engine query logs and QA forums, and combining the resulting candidate assertions with statistical cues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 26 publications
(23 reference statements)
1
69
0
Order By: Relevance
“…We assume that the confidence in a fact or rule in our common sense knowledge base (KB in the following) typically arises from a large number of human users via crowd-sourcing like in ConceptNet [35,7], NLP-analyzed scraped text from the web like NELL [27], and/or combining different knowledge bases with weights like in [14] and [7] or assigned to the equivalence of name pairs in the vocabulary like in [28] and [19]. There is recent progress towards making knowledge bases for common sense reasoning where the relation strengths (typicality, saliency) have been empirically evaluated [7,33].…”
Section: Sources Representation and Meaning Of Statements Confidences And Dependenciesmentioning
confidence: 99%
“…We assume that the confidence in a fact or rule in our common sense knowledge base (KB in the following) typically arises from a large number of human users via crowd-sourcing like in ConceptNet [35,7], NLP-analyzed scraped text from the web like NELL [27], and/or combining different knowledge bases with weights like in [14] and [7] or assigned to the equivalence of name pairs in the vocabulary like in [28] and [19]. There is recent progress towards making knowledge bases for common sense reasoning where the relation strengths (typicality, saliency) have been empirically evaluated [7,33].…”
Section: Sources Representation and Meaning Of Statements Confidences And Dependenciesmentioning
confidence: 99%
“…The extraction pipeline is detailed in the original paper [10] and is summarized in Figure 1. We recall here the main steps.…”
Section: Quasimodomentioning
confidence: 99%
“…Resulting Data As of May 2020, Quasimodo is composed of approximately four million statements for over 95.000 different subjects, making it more than ten times bigger than ConceptNet. In [10], it was shown that its precision is significantly higher than Webchild, and that its recall significantly exceeds all other commonsense knowledge bases.…”
Section: Quasimodomentioning
confidence: 99%
See 2 more Smart Citations